Electronic Health Record Goes Personal World-wide - Li, YC; Lee, PS; Jian, WS; Kuo, CH (Yearbook of Medical Informatics, 2009)
Objective Increasing patient demand for convenient access to their own healthcare data has led to more personal use of the Electronic Health Record (EHR). With “consumer empowerment” being an important issue of EHR, we are seeing a more “patient-centric” approach of EHR from countries around the world. Researchers have reported on issues in EHR sharing including concerns on privacy and security, consumer empowerment, competition among providers, and content standards. This study attempts to analyze prior research and to synthesize comprehensive, empirically-based conceptual models of EHR for personal use.Methods We use “B2C(2B)” to represent this new behavior of EHR sharing and exchange, with “consumer” in the center stage.ResultsBased on different information sharing mechanisms, we summarized the “B2C(2B)” behavior into three models, namely, the Inexpensive data media model, the Internet patient portal model and the Personal portable device model. Models each have their own strengths and weaknesses in their ways to share patient data and to address privacy and security concerns.Conclusion Personal use of EHR under the B2C(2B) model does look promising based on our study. We started to observe a trend that governments around the world are embarking on related projects. With multiple stake-holders involved, we are only beginning to understand the complexity of such undertakings.
Keywords: Electronic health records; EHR; personal health record; PHR